A review of electrically conductive concrete heated pavement system technology: From the laboratory to the full-scale implementation. (25th April 2022) - Rahman, Md Lutfor; Malakooti, Amir; Ceylan, Halil; Kim, Sunghwan; Taylor, Peter C.
Highlights: Reviewed electrically conductive concrete (ECON) heated pavement system (HPS) technology. Discussed the material-related factors influencing the performance of ECON HPS. Analyzed all full-scale ECON HPS projects. Identified the challenges that ECON HPS technology needs to overcome. Abstract: Transportation agencies in cold regions often suffer each year economically due to a partial shutdown of their transportation networks during winter storms. Traditional passive ice and snow removal techniques using snowplows, snowblowers, snow shovels and de-icing chemicals are inefficient and hazardous to the environment and pavement. The addition of electrically-conductive fillers (ECFs) such as carbon fibers and steel fibers in a standard concrete mixture reduces electrical resistivity and enhances the resistive heating properties of electrically-conductive concrete (ECON). Under the application of electric voltage, the heat produced from ECON can melt ice and snow accumulated on the pavement. While ECON can be utilized in heated-pavement systems (HPS), field-scale implementation of ECON HPS technology is not yet ubiquitous. This study discusses the challenges that must be overcome to make ECON HPS technology economically attractive to transportation agencies.